2009
DOI: 10.1080/13607860802154499
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effectiveness of a case-specific approach to challenging behaviour associated with dementia

Abstract: Results confirm those of other studies which have used multifaceted interventions tailored to the unique needs of each case. They compare favourably with results from trials of standardized psycho-pharmacological or psychosocial approaches. More trials are needed, necessarily involving further development of robust methodologies which reflect the case-specific nature of challenging behaviour associated with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…In the main, these case-specific studies have had more rigorous methodology than trials of standardized psychosocial interventions, and have produced superior results. These include reductions in frequency and perceived severity of the target behavior and GP call outs (Davison et al, 2006); reductions in anti-psychotic use (Fossey et al, 2006); reductions in agitated behavior and increases in observed participant pleasure (Cohen-Mansfield, Libin, & Marx, 2007); and reductions in BPSD frequency and perceived severity, staff stress, hospitalizations, anti-psychotic use, and drug side effects (Bird, Llewellyn Jones, & Korten, 2009;Bird, Llewellyn Jones, Korten, & Smithers, 2007). Brechen, Murphy, James, and Codner (2013) highlight the need to examine psychological interventions as alternatives to anti-psychotic medication for the treatment of BPSD.…”
Section: Introductionmentioning
confidence: 97%
“…In the main, these case-specific studies have had more rigorous methodology than trials of standardized psychosocial interventions, and have produced superior results. These include reductions in frequency and perceived severity of the target behavior and GP call outs (Davison et al, 2006); reductions in anti-psychotic use (Fossey et al, 2006); reductions in agitated behavior and increases in observed participant pleasure (Cohen-Mansfield, Libin, & Marx, 2007); and reductions in BPSD frequency and perceived severity, staff stress, hospitalizations, anti-psychotic use, and drug side effects (Bird, Llewellyn Jones, & Korten, 2009;Bird, Llewellyn Jones, Korten, & Smithers, 2007). Brechen, Murphy, James, and Codner (2013) highlight the need to examine psychological interventions as alternatives to anti-psychotic medication for the treatment of BPSD.…”
Section: Introductionmentioning
confidence: 97%
“…However, case specificity 62 to include examination of relevant biopsychosocial interventions for the person as well as good attention to the needs of the caregiving system still appears to be the way forward for the management of CB in dementia. A functional analysis approach to interventions for CB in dementia care provides a framework for assessment and targeting of case-specific formulaic interventions.…”
Section: Overview Of Key Findings From Challenge Demcarementioning
confidence: 99%
“…15 An independent assessment of improvements in dementia care since 2009 commissioned by the Department of Health, outlines priorities for action in the final year of the 'Prime Minister's Challenge on Dementia', including the need for psychosocial and other alternatives to pharmacological management of CB, to guide commissioners or providers (see Knapp et al pp. 3,62). 302 Our programme of empirically informed knowledge about practices and recommendations for post-diagnostic service improvements that are urgently required for the management of CB in dementia care will go some way to address this priority.…”
Section: Overview Of Key Findings From Challenge Demcarementioning
confidence: 99%
See 2 more Smart Citations